Hepatitis B Core-related Antigen: An Alternative to Hepatitis B Virus DNA to Assess Treatment Eligibility in Africa. (17th May 2019) - Shimakawa, Yusuke; Ndow, Gibril; Njie, Ramou; Njai, Harr Freeya; Takahashi, Kazuaki; Akbar, Sheikh Mohammad Fazle; Cohen, Damien; Nayagam, Shevanthi; Jeng, Adam; Ceesay, Amie; Sanneh, Bakary; Baldeh, Ignatius; et al.
Abstract: Background: To eliminate hepatitis B virus (HBV) infection, it is essential to scale up testing and treatment. However, conventional tools to assess treatment eligibility, particularly nucleic acid testing (NAT) to quantify HBV DNA, are hardly available and affordable in resource-limited countries. We therefore assessed the performance of a novel immunoassay, hepatitis B core-related antigen (HBcrAg), as an inexpensive (US$ <15/assay) alternative to NAT to diagnose clinically important HBV DNA thresholds (≥2000, ≥20 000, and ≥200 000 IU/mL) and to select patients for antiviral therapy in Africa. Methods: Using a well-characterized cohort of treatment-naive patients with chronic HBV infection in The Gambia, we evaluated the accuracy of serum HBcrAg to diagnose HBV DNA levels and to indicate treatment eligibility determined by the American Association for the Study of Liver Diseases, based on reference tests (HBV DNA, hepatitis B e antigen, alanine aminotransferase, liver histopathology, and/or FibroScan). Results: A total of 284 treatment-naive patients were included in the analysis. The area under the receiver operating characteristic curve (AUROC), sensitivity, and specificity of serum HBcrAg were 0.88 (95% confidence interval [CI], .82–.93), 83.3%, and 83.9%, respectively, to diagnose HBV DNA ≥2000 IU/mL; and 0.94 (95% CI, .88–.99), 91.4%, and 93.2% for ≥200 000 IU/mL. A simplified treatment algorithm using HBcrAg without HBV DNA showed high AUROC (0.91 [95% CI, .88–.95]) with a sensitivity of 96.6% and specificity of 85.8%. Conclusions: HBcrAg might be an accurate alternative to HBV DNA quantification as a simple and inexpensive tool to identify HBV-infected patients in need of antiviral therapy in low- and middle-income countries. Abstract : Limited access to hepatitis B virus (HBV) DNA quantification represents a key barrier to global HBV elimination. We demonstrated high diagnostic accuracy of a low-cost immunoassay, hepatitis B core-related antigen, to diagnose HBV DNA levels.